A new approach based on genetic algorithm for computation offloading optimization in multi-access edge computing networks - Myyara, Marouane; Lagnfdi, Oussama; Darif, Anouar; Farchane, Abderrazak (Institute of Advanced Engineering and Science, 2024)
The proliferation of smart devices and the increasing demand for resource-intensive applications present significant challenges in terms of computational efficiency, leading to surge in data traffic. While cloud computing offers partial solutions, its centralized architecture raises concerns about latency. Multi-access edge computing (MEC) emerges as promising alternative by deploying servers at the network edge to bring computations closer to user devices. However, optimizing computation offloading in the dynamic MEC environment remains a complex challenge. This paper introduces novel genetic algorithm-based approach for efficient computation offloading in MEC, considering processing and transmission delays, user preferences, and system constraints. The proposed approach integrates computation offloading and resource allocation algorithm based on evolutionary principles, combined with a greedy strategy to maximize overall system performance. By utilizing genetic algorithms, the proposed method enables dynamic adaptation to changing conditions, eliminating the need for intricate mathematical models and providing an appealing solution to the complexities inherent in MEC. The urgency of this research arises from the critical need to enhance mobile application performance. Simulation results demonstrate the robustness and efficacy of our approach in achieving near-optimal solutions while efficiently balancing computation offloading, minimizing latency, and maximizing resource utilization. Our approach offers flexibility and adaptability, contributing to advancement of MEC networks and addressing the requirements of latency-sensitive applications.